Mutation yellow in agouti loci prevents age-related increase of skeletal muscle genes regulating free fatty acids oxidation - Y. V. Piskunova; A. Y. Kazantceva; A. V. Baklanov; N. M. Bazhan (Вавиловский журнал генетики и селекции, 2018)
The lethal yellow mutation in agouti loci (Ay mutation) reduces the activity of melanocortin (MC) receptors and causes hyperphagia, obesity and type two diabetes mellitus in aging mice (Ay mice). It is unknown if changes in distinct elements of the metabolic system such as white adipose tissue (WAT) and brown adipose tissue (BAT), and skeletal muscle will manifest before the development of obesity. The aim of this work was to measure the relative gene expression of key proteins that regulate carbohydrate-lipid metabolism in WAT, BAT and skeletal muscle in Ay mice before the development of obesity. C57Bl/6J mice bearing a dominant autosomal mutation Ay (Ay /a mice) and mice of the standard genotype (a/a mice, control) have been studied in three age groups: 10, 15 and 30 weeks. The relative mRNA level of genes was measured by real-time PCR in skeletal muscles (uncoupling protein 3 (Ucp3) and carnitine palmitoyl transferase 1b (Cpt1b) (free fatty acids oxidation), solute carrier family 2 (facilitated glucose transporter), member 4 (Slc2a4) (glucose uptake)), in WAT lipoprotein lipase (Lpl) (triglyceride deposition), hormone-sensitive lipase (Lipe) (lipid mobilization), and Slc2a4 (glucose uptake)), and in BAT: uncoupling protein 1 (Ucp1) (energy expenditure). The expression of Cpt1b was reduced in young Ay mice (10 weeks), there was no transient peak of transcription of Cpt1b, Ucp3 in skeletal muscle tissue and Lipe, Slc2a4 in WAT in early adult Ay mice (15 weeks), which was noted in а/а mice. Reduction of the transcriptional activity of the studied genes in skeletal muscle and white adipose tissue can initiate the development of melanocortin obesity in Ay mice.